Achieving Balanced Crystallinity of Donor and Acceptor by Combining Blade‐Coating and Ternary Strategies in Organic Solar Cells. Issue 51 (15th October 2018) - Zhang, Lin; Xu, Xianbin; Lin, Baojun; Zhao, Heng; Li, Tengfei; Xin, Jingming; Bi, Zhaozhao; Qiu, Guanxian; Guo, Shengwei; Zhou, Ke; Zhan, Xiaowei; Ma, Wei
Abstract: As a prototype tool for slot‐die coating, blade‐coating exhibits excellent compatibility with large‐area roll‐to‐roll coating. A ternary organic solar cell based on PBDB‐T:PTB7‐Th:FOIC blends is fabricated by blade‐coating and exhibits a power conversion efficiency of 12.02%, which is one of the highest values for the printed organic solar cells in ambient environment. It is demonstrated that blade‐coating can enhance crystallization of these three materials, but the degree of induction is different (FOIC > PBDB‐T > PTB7‐Th). Thus, the blade‐coated PBDB‐T:FOIC device presents much higher electron mobility than hole mobility due to the very high crystallinity of FOIC. Upon the addition of PTB7‐Th into the blade‐coated PBDB‐T:FOIC blends, the crystallinity of FOIC decreases together with the corresponding electron mobility, due to the better miscibility between PTB7‐Th and FOIC. The ternary strategy not only maintains the well‐matched crystallinity and mobilities, but also increases the photocurrent with complementary light absorption as well as the Förster resonant energy transfer. Furthermore, small domains with homogeneously distributed nanofibers are observed in favor of the exciton dissociation and charge transport. This combination of blade‐coating and ternary strategies exhibits excellent synergistic effect in optimizing morphology, showing great potential in the large‐area fabrication of highly efficient organic solar cells. Abstract : A balanced crystallinity of donor and acceptor is finely controlled by combining blade‐coating and ternary strategies in a PBDB‐T:PTB7‐Th:FOIC‐based organic solar cell, resulting in well‐matched hole and electron mobilities with a power conversion efficiency of 12.02%.